Becoming an International Brand: A Case Study of Starbucks - Azriuddin, Muhammad; Kee, Daisy Mui Hung; Hafizzudin, Muhammad; Fitri, Muhamad; Zakwan, Muhammad Afiq; AlSanousi, Dalal; Kelpia, Aman; Kurniawan, Olivia (Journal of The Community Development in Asia, 2020)
This paper aims to investigate how Starbucks becomes the best coffee shop worldwide and how the organization overcomes its challenges and succeed to become an international brand. Starbucks is a popular coffee restaurant from the beginning but has just become a famous brand worldwide. Starbucks has over 20,000 stores in 62 countries around the world. In 1971 Starbucks opened its first store in Seattle’s Pike Place Market. Howard Schultz joins Starbucks as a director of Retail Operations and Marketing. Starbucks focuses on its mission “Inspire and nurture the human spirit-one person, one cup, and one neighbourhood at a time. Starbucks provides a variety of drinks from hot to cold, and foods. The most famous beverage is Frappuccino® Blended Beverages. Starbucks makes a beverage menu depending on the customer's request to meet their satisfaction. Starbucks emphasizes on high-quality service from the store environment to the work environment. Starbucks promotes its products through mass media such as advertising at the television, social media, billboards, and coupon card. The paper concludes with some recommendation.